2019
DOI: 10.7324/japs.2019.90508
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of methanolic and flavonoid-rich leaf extracts of Synsepalum dulcificum (Danielli) on lead-acetate-induced toxicity in Wistar albino rats

Abstract: The present study aims to evaluate the protective effect of methanolic leaf extract and flavonoid-rich leaf extract of Synsepalum dulcificum on lead-acetate-induced toxicity in Wistar albino rats. Forty-five animals were distributed into nine groups with five animals apiece. Group 1 served as the control and was given only distilled water throughout the course of the study. Group 2 served as the lead-induced group and was administered 50 mg/kg lead-acetate. Groups 3-8 were co-administered 50 mg/kg lead-acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…12,27 Exposure to lead acetate can increase free radicals in the body. 16,[28][29][30] Increased free radicals lead to a rise in lipid peroxidation, [31][32][33] one of the remaining lipid peroxidations often found is Malondialdehyde. [17][18][19] Previous research has shown that exposure to lead acetate leads to elevated levels of blood Malondialdehyde.…”
Section: Discussionmentioning
confidence: 99%
“…12,27 Exposure to lead acetate can increase free radicals in the body. 16,[28][29][30] Increased free radicals lead to a rise in lipid peroxidation, [31][32][33] one of the remaining lipid peroxidations often found is Malondialdehyde. [17][18][19] Previous research has shown that exposure to lead acetate leads to elevated levels of blood Malondialdehyde.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment lasted 8 weeks. The rats were subjected to lead acetate for eight weeks to simulate subchronic lead exposure and adequate induction of lead intoxication according to Obafemi et al, (2019).…”
Section: Experimental Designmentioning
confidence: 99%